PENGEMBANGAN MEDIA AUDIO VISUAL ASHATAL (ARAHAN SHALAT DIGITAL) BAGI SISWA KELAS II SD - Rika Luviana; Dina Nuryani; Shelly Ainun Maulida; Ani Nur Aeni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the development of ASHATAL audio-visual media (Digital Prayer Directions) which aims to help second-grade elementary school students understand the material regarding prayer procedures and readings. It also helps teachers to deliver teaching materials by using a digital platform so that space and time limitations can be overcome. The research method used is theDesign & Development (D&D) method by using the ADDIE model. In the analysis stage, three main aspects were the analysis of learning materials, users, and the devices used in the research. Media design developed two components, audio and visual, as a digital book application. The ASHATAL audio-visual media (Digital Prayer Directions) was tried out to the Islamic Religious Education (PAI) teachers and the second-grade students at a public elementary school in North Sumedang District. And then the material experts obtained an assessment of the used media development. Based on the product assessment, it was obtained validation from material experts with an average percentage of 100% regarding the content of the material and the quality of the media. The assessment of Islamic Religious Education (PAI) teachers showed an average percentage of 100% regarding the content of the material and the quality of the media. Subsequently, the students’ assessment showed an average percentage of 86%. It proved that the ASHATAL audio-visual media (Digital Prayer Directions) was very suitable for elementary school students to use, especially as a medium that could help teachers in delivering teaching materials to students.